Globalization of the Power Sector as Factor for Sustainable Development and Energy Security - Shvets, Nickolay; Kolesnik, Georgy; Philippova, Alina (International Journal of Energy Economics and Policy, 2019)
The problem of ensuring that the entire world population has access to energy sources is well known. One of the approaches to solving this problem is the formation of interstate power connections. This article focuses on how to measure the effectiveness of interstate power connection projects in terms of ensuring the sustainable development of countries and regions of the world. In the article, we develop a mathematical model of synergy effects driven by creating interstate power connection. The applicability of the model is demonstrated by the example of a promising energy association of the Eurasian Economic Union (EAEU). Keywords: globalization; sustainability; energy; Eurasian Economic Union; sustainable energy; energy security. JEL Classifications: O13, P18, Q1 DOI: https://doi.org/10.32479/ijeep.8512